Neonatal mice exposed to a high-fat diet in utero influence the behaviour of their nursing dam. Issue 1891 (21st November 2018) - Baptissart, Marine; Lamb, Harold E.; To, Kimberly; Bradish, Christine; Tehrani, Jesse; Reif, David; Cowley, Michael
Abstract : The behaviour of a nursing dam influences the development, physiology, and behaviour of her offspring. Maternal behaviours can be modulated both by environmental factors, including diet, and by physical or behavioural characteristics of the offspring. In most studies of the effects of the environment on maternal behaviour, F0 dams nurse their own F1 offspring. Because the F1 are indirectly exposed to the environmental stressor in utero in these studies, it is not possible to differentiate between effects on maternal behaviour from direct exposure of the dam and those mediated by changes in the F1 as a consequence of in utero exposure. In this study, we used a mouse model of high-fat (HF) diet feeding, which has been shown to influence maternal behaviours, combined with cross-fostering to discriminate between these effects. We tested whether the diet of the F0 dam or the exposure experienced by the F1 pups in utero is the most significant predictor of maternal behaviour. Neither factor significantly influenced pup retrieval behaviours. However, strikingly, F1 in utero exposure was a significant predictor of maternal behaviour in the 15 min immediately following pup retrieval while F0 diet had no discernable effect. Our findings suggest that in utero exposure to HF diet programmes physiological changes in the offspring which influence the maternal behaviours of their dam after birth.